2022
DOI: 10.1021/jacs.2c04101
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Formal Nucleophilic o-Cresolylation with Morita–Baylis–Hillman Carbonates of 2-Cyclohexenones via Palladium Catalysis

Abstract: Here we report an asymmetric formal nucleophilic o-cresolylation reaction with the Morita–Baylis–Hillman (MBH) carbonates from 2-cyclohexanones and diverse aldehydes under palladium catalysis, by in situ generation of electron-neutral and HOMO-raised η2-Pd­(0)-dienone complexes via an oxidative insertion/π–σ-isomerization/β-H elimination activation sequence. The subsequent umpolung vinylogous addition to a variety of imines is realized upon Pd(0)-mediated π-Lewis base catalysis, finally furnishing o-cresolylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…While similar regioselective umpolung addition reaction of the MBH carbonates from 2-cycloheptenone was observed, 4 it was intriguing that the MBH carbonates 1 from 2-cyclopentenone 6 exhibited a completely different regioselective reaction pattern under palladium catalysis. It was worth noting that the η 2 -Pd(0)-dienone complexes II at the exo-double bond were favorably generated, rendering the endo-double bond as a HOMO-raised dienophile in combination with a suitable electron-deficient heterodiene partner (Scheme 1c).…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…While similar regioselective umpolung addition reaction of the MBH carbonates from 2-cycloheptenone was observed, 4 it was intriguing that the MBH carbonates 1 from 2-cyclopentenone 6 exhibited a completely different regioselective reaction pattern under palladium catalysis. It was worth noting that the η 2 -Pd(0)-dienone complexes II at the exo-double bond were favorably generated, rendering the endo-double bond as a HOMO-raised dienophile in combination with a suitable electron-deficient heterodiene partner (Scheme 1c).…”
mentioning
confidence: 81%
“…3 In contrast, recently we uncovered a new transformation pathway with the MBH carbonates derived from 2-cyclohexenone under cascade palladium catalysis, by in situ generating the key η 2 -Pd(0)dienone complexes I in the absence of nucleophiles. 4 The π-Lewis base activation 5 of Pd(0) umpolunged the reactivity of exo-β-carbon of the enone motif based on the principle of vinylogy, which could attack the imines enantioselectively to yield the formal o-cresolylation products after further cascade transformations (Scheme 1b).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Commonly used ( S )-BINAP L1 , as well as its analog ( S )-Segphos L2 , could promote the reaction but exhibited low efficiency in both reactivity and stereoselectivity (entries 2 and 3). SPINOL-derived phosphoramidite ligand L3 improved the yield and enantioselectivity significantly, albeit with poor diastereoselectivity (entry 4) . Further screenings of more ligands indicated that Tang’s chiral P-based ligand L4 and Trost’s phosphine-amide ligand L5 were ineffective (entries 5 and 6, respectively), while 1,2-aminoalcohol-drived bifunctional ligand L6 provided cis - 3a as the single diastereomer in a fair yield but with remarkable enantioselectivity (entry 7) .…”
mentioning
confidence: 99%